Determining the Diversity and Density of Zooplanktons of Kolar Reservoir in India - Chaudhary, Ruchira; Pillai, Rachana S. (Research Aspects in Biological Science Vol. 3, 2022)
The goal of this study is to determine the zooplankton diversity and density in the Kolar reservoir in Bhopal, M.P. Samples were taken from three distinct reservoir sampling locations, and the density of the planktons was calculated. During the study year of 2007-2008, there were three primary groups of zooplanktons in the reservoir. Protozoa, Rotifera, and Crustacea are their names. Crustacea had the highest average density, with 950org/l. The maximum density was found in the month of June, while the lowest density was found in the month of November. The study of zooplanktons is important for any water body as they are important bioindicators of water pollution.